Financial Leverage Analysis of PT Gudang Garam Tbk: A Five-Year Study - Pamanda, Dyasturi Fani; Jaya , Amir; Mongan , Claudio Julio (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the financial leverage trends of PT Gudang Garam Tbk during the 2019–2023 period and evaluates its relationship with profitability, measured by Return on Equity (ROE), and dividend policy, represented by Dividend Per Share (DPS). Using a descriptive quantitative approach and secondary financial data, the research applies financial ratio analysis to assess performance dynamics. Findings indicate that the company maintained a stable leverage level with low interest burden, suggesting a conservative financing structure. While ROE showed a downward trend, the decline was primarily driven by operational income fluctuations rather than debt utilization. DPS distribution remained relatively consistent, reflecting managerial commitment to shareholder returns despite varying earnings. The results suggest that financial leverage was not a dominant factor influencing profitability during the observed period. Instead, operational efficiency played a more critical role in shaping the company’s financial outcomes. This analysis contributes to a deeper understanding of capital structure decisions in capital-intensive industries and offers practical implications for corporate financial strategy and investor confidence.